STUDI TENTANG PENGETAHUAN SIKAP DAN PERILAKU PENDERITA INFEKSI SALURANPERNAPASAN AKUT (ISPA) DI WILAYAH KERJA UPTD PUSKESMAS BANJARMANGU 2 - Barni Barni; Seli Puji Rahayu (Jurnal Ilmiah Medsains, 2022)
ARI is still a public health problem today. Puskesmas Banjarmangu 2 is one of the Puskesmas inBanjarnegara Regency which still has ARI disease problems. Based on observations from January toMarch 2022, the prevalence of ARI is still quite high. The purpose of this study was to find out anddescribe the description of knowledge, attitudes and behavior as well as the physical condition of thehouse of patients with ARI (Acute Respiratory Infection) in the Work Area of the Banjarmangu HealthCenter 2. This study was included in a descriptive study with a cross sectional method. The populationin this study were patients with ARI Puskesmas Banjarmangu 2 who had checked themselves at thePuskesmas in the period March 2022, namely 58 people with random sampling technique. The data usedin this study are primary data obtained from questionnaires and field observations as well as secondarydata from previous studies. Data analysis was carried out in a univariate way. The results showed thatthe patient's knowledge level was good (67.2%), the patient's attitude was good (93.1%), and thepatient's behavior was good (87.9%).